MASKULINISASI IKAN CUPANG (Betta sp.) MENGGUNAKAN EKSTRAK TESTIS SAPI MELALUI PERENDAMAN DENGAN DOSIS PERENDAMAN YANG BERBEDA - Yusifar Fathana Saputra; Muhammad Junaidi; Bagus Dwi Hari Setyono (Jurnal Media Akuakultur Indonesia, 2022)
Ornamental fish is a fish that is much favored by the public because it has a beautiful color. The demand for ornamental fish is increasing every year both in the domestic and international markets, based on data from the KKP in 2018 the export value of hyacinth reached USD 32.23 million and in 2020 Indonesia targets to produce 1.8 billion ornamental fish. One of the ornamental fish that is much favored by the public is Betta fish (Betta sp). From an economic point of view, male betta fish cultivation is less profitable because of its poor body color and morphology. Male betta fish are more popular than female fish, because they have advantages in terms of color and morphology. Based on the results of the study, it was found that the highest male sex presentation of betta fish was in treatment P4 with a total of 91.11% followed by treatment P5 with a total of 73.33% treatment P3 78.89% to treatment P2 58.89% male and followed by male sex presentation the lowest was found in treatment P1 with a total of 35.56%.